TLR4 and C5aR crosstalk in dendritic cells induces a core regulatory network of RSK2, PI3Kβ, SGK1, and FOXO transcription factors. Issue 4 (1st October 2017) - Zaal, Anouk; Nota, Benjamin; Moore, Kat S; Dieker, Miranda; van Ham, S Marieke; ten Brinke, Anja
Abstract : Identification of a central regulatory network formed by FOXO1, FOXO3, RSK2, PI3Kβ 2, and SGK1 upon C5aR and TLR4 crosstalk in human monocyte-derived DCs. Abstract: Crosstalk between complement component 5a receptors (C5aRs) and TLRs in dendritic cells (DCs) occurs upon pathogen invasion; however, studies on C5aR and TLR crosstalk mainly focused on the modulating effect of C5a on TLR-induced cytokine production. To elucidate the breadth of C5aR and TLR4 crosstalk, the effect of simultaneous treatment with C5a and LPS was investigated in human monocyte-derived DCs (moDCs) 2 h after stimulation using whole transcriptome sequencing analysis. Although the effect of C5a on hallmark genes defining TLR4-induced DC maturation was limited at this time point, RNA sequencing analysis revealed a great variety of novel C5a targets, of which many interfere with TLR4-mediated immune activation. Analysis of functional relationships among these genes uncovered induction of a central immune regulatory network upon C5aR and TLR4 crosstalk, involving the transcription factors forkhead box (FOX)O1 and FOXO3 and the signaling molecules serum- and glucocorticoid-inducible kinase (SGK1), ribosomal S6 kinase 2 (RSK2), and PI3Kβ. C5aR and TLR crosstalk, furthermore, yielded down-regulation of mainly proinflammatory network branches, including IL-12B, IL-2Rα (IL-2RA), and jagged 1 (JAG1) and cooperative induction of predominantly anti-inflammatory network branches, including sphingosine kinase 1 (SPHK1), β2 adrenergic receptor (ADRB2), gastric inhibitory polypeptide receptor (GIPR), and four-and-a-half Lin11, Isl-1, and Mec-3 domains protein 2 (FHL2). Together, these data point toward induction of generalized immune regulation of DC function. Motif enrichment analysis indicate a prominent role for basic leucine zipper (bZIP) and IFN regulatory factor 4 (IRF4) transcription factors upon C5aR and TLR4 crosstalk. Additionally, differences were observed in the modulating capacity of C5a on DCs in the absence or presence of a pathogen (TLR stimulus). Our findings shed new light on the depth and complexity of C5aR and TLR4 crosstalk and provide new foci of research for future studies.